Nursing professionals in the context of the COVID-19 pandemic: experience report - de Albuquerque , Nataniele; Mirella da Silva , Thaísa; Maria de Oliveira Costa Meneses , Suzana; Maria de Oliveira Silva , Sâmela; Alves e silva Diniz , Clebiana; de Andrade Rocha, Tainan; Maria Pacheco Lins Magalhães , Julia; Silva de Brito, Poliana; de Araújo Holanda, Manuelle; dos Santos Nunes, Eliane (Seven Editora, 2023)
The emergence of the Covid-19 pandemic has multiplied fears and uncertainties among pregnant women, especially among nurses who experienced pregnancy and the puerperium during the pandemic, due to the greater vulnerability resulting from the specifics of work. Objective: To report the experience of nurses from the Oncology Unit of the HUPAA, pregnant women in the context of the COVID-19 pandemic. Method: This is a descriptive, exploratory, experience report type study. Results: Technological innovation, through remote work, provided a beneficial experience for pregnant nurses, as it allowed them to protect and protect this group, ensuring greater safety for the mother-child binomial. DOI: https://doi.org/10.56238/tfisdwv1-066